2022
DOI: 10.7759/cureus.28885
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the POPBL (Patient-Oriented Problem-Based Learning) Module in Pathology: A Comparative Analysis of Performance and Perception Among Second-Year Pathology Students

Abstract: Background and objectiveEmploying the POPBL (Patient-Oriented Problem-Based Learning) method to teach students offers a fresh take on the classroom experience. It helps to enhance the motivation of the students, improves knowledge, self-learning behavior, and clinical reasoning, and also helps to promote long-lasting memory. In our medical college, we adopted a newer technology-oriented method with the use of case history, laboratory findings, a gross specimen of the same case, microscopic live sessions via De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Overall, our findings were in accordance with previous studies, in which the case-based PBL could improve the student' grades and be adapted to different courses. [19][20][21][22][23] With the willingness of good performances in the class, students would strengthen their independent learning and review carefully, which was sometimes beyond the goal designed. [24] Students' feedback of the integrated PBL for the basic and clinical medicine courses were collected.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our findings were in accordance with previous studies, in which the case-based PBL could improve the student' grades and be adapted to different courses. [19][20][21][22][23] With the willingness of good performances in the class, students would strengthen their independent learning and review carefully, which was sometimes beyond the goal designed. [24] Students' feedback of the integrated PBL for the basic and clinical medicine courses were collected.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of medical school is to provide students with the knowledge necessary to comprehend the underlying physiological changes that manifest as illness [ 13 ]. The basic goal of medical education is to produce professionals who are up to the task of treating patients [ 14 ]. OSPE assisted students who performed below or above average on tests of cognitive, psychomotor, and attitude skills, suggesting that it is a reliable strategy with a strong capacity to distinguish between various groups of pupils.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the outcome of student comfort, test grades would also be beneficial to measure to provide an objective performance metric. Studies have shown that case-based learning can be associated with improved pathology examination scores [ 5 ] and improved NBME examination scores [ 6 ]. In addition, near-peer education has been correlated with increased scores in anatomy examinations [ 13 , 14 ] and improved USMLE examination scores as well [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Average bipolar Likert scale responses and standard deviations for each course pre survey and post survey for both the intervention and control group were calculated as well as the average Likert response and standard deviation across all three courses. These were obtained by converting the scale that ranged from 1 to 10, with 1 being strongly disagree to 10 being strongly agree to a 5-point scale where the numbers 1 and 2 represented strongly disagree (1 on the new scale), 3 and 4 represented slightly disagree (2), 5 and 6 represented neutral (3), 7 and 8 represented slightly agree (4), and 9 and 10 represented strongly agree (5). Changes in average Likert responses between pre and post surveys for each course, as well cumulatively, for both the intervention and control groups, were calculated and reported to three decimal places.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation